Lipid peroxides level in the Indonesian elderly (Medical Journal of Indonesia, 2005)
A cross-sectional study was done to see the possible association of plasma lipid peroxides in the elderly with age and other factors. Plasma lipid peroxides is a product of free radical reactions which according to the latest theory of aging is the cause of aging process. Lipid peroxides were also found high in coronary heart disease. Four hundred forty relatively healthy elderly, age 55-85 years, were randomly chosen from free living elderly under guidance of health care centers (PUSKESMAS) in Jakarta. Anamnesis and physical examination were done in the morning in the health centers. Blood samples were taken in fasting conditions, plasma lipids and lipid peroxides were measured according to standard methods. There was an age difference of lipid peroxides level in the elderly, which increased with age up to 70 years old. Elderly 70 years old and over had low plasma lipid peroxides. The level was not related to high plasma lipids. Higher level was found when more chronic degenerative diseases were found. (Med J Indones 2005; 14: 71-7) Keywords: lipid peroxides, aging